KONSEP REWARD DAN PUNISHMENT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Fahrezi, Muhammad Adnan; Maulana, Muhamad Pandu; Nurwahid, Muhammad Salman; Victorynie, Irnie (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
In education, the concepts of reward and punishment are very important, especially for influencing student behavior and encouraging them to learn. The increasing difficulty in managing discipline and motivation in the classroom has made this issue urgent. The purpose of this research is to evaluate the effectiveness of rewards and punishments in behavior formation, as well as how they impact students' desire to learn. This research uses a qualitative approach method and the research location is an elementary school in Bekasi Regency. Data were collected through observations and interviews. The purpose of this method is to gain a better understanding of the perceptions and experiences of students and teachers regarding the implementation of rewards and punishments. The research results show that rewards tend to increase students' intrinsic motivation. Punishments have different effects depending on the type and frequency of the punishment. If done correctly, rewards and punishments can work well to improve discipline and enhance student motivation. What is expected from this research is that it will help educators develop more proportional and positively impactful reward and punishment methods.